IMPLEMENTASI KONSEP MULTIPLE INTELLIGENCES DALAM PRAKTIK PEMBELAJARAN GURU DI SDN 07 LEMBAH MELINTANG - Dewi Fitriana; Fitria Nilda; Siska Lanora; Syatria Hasni; Yustina; Ratnawilis; Rinda Riska (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze teachers’ practices in mapping students’ intelligence profiles and optimizing their potential through adaptive instructional strategies at SDN 07 Lembah Melintang. Employing a qualitative approach with a case study design, the research explores teachers’ understanding of intelligence, the integration of intelligence mapping into classroom instruction, and the strategies used to develop students’ potential through classroom observations, in-depth interviews, and document analysis. The findings indicate that teachers interpret intelligence pragmatically based on students’ learning behaviors and responses, while intelligence mapping is conducted informally through daily observations. Despite the absence of structured assessment instruments, teachers successfully integrate their understanding into instructional practices by applying differentiated activities, multisensory approaches, collaborative learning, and both enrichment and individualized support. The study concludes that teachers’ practices already reflect responsiveness to diverse intelligence profiles, although methodological reinforcement is needed to implement more systematic and sustainable intelligence mapping and potential development.